Drug Induced Hepatitis pada Tuberkulosis Paru dengan Multisite Tuberkulosis Ekstraparu : [Drug-Induced Hepatitis in Mixed Pulmonary and Extrapulmonary Tuberculosis] - Made Agustya Darma Putra Wesnawa; Tutik Kusmiati (Jurnal Respirasi, 2019)
Background: Tuberculosis (TB) continues to be a major health problem in developing country. Lung is the most common site for Mycobacterium tuberculosis (MTB) infection, but dissemination may occur to any part of the body resulting in extrapulmonary TB. Hepatotoxicity is one of the most frequent adverse events that occur during TB treatment. Case: A 35-year-old female patient came with cough, dyspnea, fever, abdominal pain, history of mass in right inguinal lymph node, and malnutrition. Histopathology from excisional biopsy of inguinal lymph node showed granulomatous inflammation. Computed tomography of abdomen showed intraabdominal TB. Chest X-ray showed right pleural effusion, with exudate pleural fluid and mononuclear dominant. After 1 week consuming antituberculous drug, patient got nausea and vommiting, increased of ALT and AST, total and direct bilirubin. Antituberculous drug was stopped and switched to levofloxacin, ethambutol, and streptomycin. After clinical improvement and liver function return to normal, desensitization of rifampicin and isoniazide was started. Desensitization started with rifampicin for three days, and followed with isoniazide for three days. In total, the patient got rifampicin, isoniazide, and ethambutol for 9 months. Evaluation of treatments are clinical improvement and weight gain. Acid fast baccili sputum was negatif, no pleural effusion on chest X-ray, and normal abdominal ultrasound. Conclusion: MTB can spread to other organs which cause multisite extrapulmonary TB. Side effect can occur during TB treament, and this is not the reason to stop the therapy. Individual ATD therapy shows good response in this case.